Archival Classification and Knowledge Organization: Theoretical Possibilities for the Archival Field - Bragato Barros, Thiago Henrique [UNESP]; Moraes, João Batista Ernesto de [UNESP] (Ergon-verlag Gmbh, 2012)
The main goal of this study is to outline a possible relation between archival classification and knowledge organization theory. In this sense, we seek to contribute to the conceptual classification in Archival Science, since there is a lack of systematization about archival classification; not just classification, but even the study of historical and conceptual aspects of the discipline. In the context of knowledge organization there is a considerable amount of research on how to build classification schemes and indexing systems that can help contribute to and expand archival classification theory. In order to comprehend this vast field of theories and methodologies we construct a parallel comparing the classification concepts in both areas and analyzing these concepts.